2015
DOI: 10.4172/2153-2435.1000367
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Synergistic Potential of Eugenol: A Review

Abstract: Eugenol (1-allyl-4-hydroxy-3-methoxybenzene) is the phenolic component of essential oil and the main constituent of Eugenia caryophyllata, Ocimmum gratissimum and several others medicinal plant. In view of its nonmutagenic and non-carcinogenic properties, eugenol is generally regarded as safe by the Food and Agricultural Organization of the United Nations. Eugenol has been recently shown to be effective for antimicrobials and treatment of different life threatening diseases including sepsis, leishmaniasis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 63 publications
1
26
0
4
Order By: Relevance
“…Eugenol (4-allyl-2-methoxyphenol; C10H12O2) is a natural product with broad therapeutic properties that is extracted from Eugenia cariophyllata and other plants. Eugenol belongs to the phenlypropanoid family and has a molecular weight (MW) of 164.2 g/mol with a pKa = 10.19 at 25°C (Charan-Raja et al, 2015). This plant has been used as an antioxidant (it inhibits the generation of active oxygen species in endothelial cells), antimycotic, antiviral, antiparasitic, antibiotic, and in deinsectation (Kong et al, 2014c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol (4-allyl-2-methoxyphenol; C10H12O2) is a natural product with broad therapeutic properties that is extracted from Eugenia cariophyllata and other plants. Eugenol belongs to the phenlypropanoid family and has a molecular weight (MW) of 164.2 g/mol with a pKa = 10.19 at 25°C (Charan-Raja et al, 2015). This plant has been used as an antioxidant (it inhibits the generation of active oxygen species in endothelial cells), antimycotic, antiviral, antiparasitic, antibiotic, and in deinsectation (Kong et al, 2014c).…”
Section: Introductionmentioning
confidence: 99%
“…iD It has been noted that eugenol at low concentrations exerts a reducing effect on synaptic transmission of the neuromuscular zone, thus being capable of producing anesthesia (Charan-Raja et al, 2015). However, Dal Bó and colleagues (2013) demonstrated that the analgesic mechanism of action can involve the opioid system, glutaminergic receptors (Kainate and AMPA), and the inhibition of tumor necrosis factor alpha (TNF-α); therefore, it can be an important component in the treatment of acute pain.…”
Section: Introductionmentioning
confidence: 99%
“…El eugenol es un alilbenceno (Figura 1) obtenido a partir de diversas plantas medicinales y aromáticas, siendo las más representativas: Syzygium aromaticum, Myristica fragrans, Cinnamomum tamala, Zygium aromaticum y especies del genero Ocimum (Charan-Raja et al, 2015). Diversos estudios han demostrado sus propiedades antifúngicas (Charan-Raja et al, 2015;Kong et al, 2014). Sin embargo, aún no se ha esclarecido su mecanismo de acción (Charan-Raja et al, 2015;Kong et al, 2014;Abbaszadeh et al, 2014).…”
Section: Introductionunclassified
“…Diversos estudios han demostrado sus propiedades antifúngicas (Charan-Raja et al, 2015;Kong et al, 2014). Sin embargo, aún no se ha esclarecido su mecanismo de acción (Charan-Raja et al, 2015;Kong et al, 2014;Abbaszadeh et al, 2014).…”
Section: Introductionunclassified
“…Asimismo, diversos estudios demuestran que el eugenol posee actividad anti-inflamatoria, analgésica, antioxidante, antimicrobiana, antiparasitaria, anticancerígena y antifúngica. Por lo tanto, es de suma importancia estudiar el potencial farmacológico del eugenol [4][5].…”
Section: Introductionunclassified